Energy dissipation of P- and S-waves in fluid-saturated rocks: An overview focusing on hydraulically connected fractures - Rubino, J. Germán (2015)
An important characteristic of fractured rocks is their high seismic attenuation, which so far has been mainly attributed to wave-induced fluid flow (WIFF) between the fractures and the embedding matrix. The influence of fracture connectivity on seismic attenuation has, however, recently, only been investigated. Numerical compressibility and shear tests based on Biot’s quasi-static poro-elastic equations illustrate that an important manifestation of WIFF arises in the presence of fracture connectivity. The corresponding energy loss, which can be significant for both P- and S-waves, is mainly due to fluid flow within the connected fractures and is sensitive to the permeabilities as well as the lengths and intersection angles of the fractures. Correspondingly, this phenomenon contains valuable information on the governing hydraulic properties of fractured rocks and hence should be accounted for whenever realistic seismic models of such media are needed.